Interval of the existence of positive solutions for a boundary value problem for system of three second-order differential equations - Aleksejs Antoņuks; Sergey Smirnov (Electronic Journal of Qualitative Theory of Differential Equations)
The aim of this paper is to estimate an interval of the existence of positive solutions for a boundary value problem for the system of three nonlinear second-order ordinary differential equations. Krasnosel'skiĭ–Precup fixed point theorem is used to determine this interval theoretically. For Dirichlet boundary conditions theoretical result is compared with result obtained numerically.